Pengaruh Institutional Ownership, Firm Size, Dan Solvability Terhadap Earnings Management - Jesslyn Yeo, Yanti (Jurnal Paradigma Akuntansi, 2022)
This study aims to test empirically the effect of institutional ownership, firm size, and solvability on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. This study uses a purposive sampling method with a total of 75 companies. The entire testing process to perform data analysis in this study uses Eviews (Econometrical Views) 11 and Microsoft Excel 2010. The results show that there is a significant and positive effect of solvability and firm size on earnings management. Meanwhile, institutional ownership does not have a significant effect on earnings management. The implication of this research is the need for supervision of liabilities and matters that can affect firm size so it is not too high for minimize the occurrence of manipulation of earnings.